Pancasila as a Moral Foundation in the Field of Education in Facing Intolerance in Indonesia - Susilawati, Marietta.D.; Indrawati, Etty; Weenas, Andi Harunsyah Peter Noel (Westscience Press, 2025)
Pancasila as the philosophical and ethical basis of the state has a fundamental role in maintaining social harmony and strengthening the unity of the Indonesian nation amid the threat of intolerance. Intolerance, whether in the form of discrimination based on ethnicity, religion, race, or political views, can threaten national integration if not handled comprehensively. This research aims to examine how the values of Pancasila can be applied as an ethical foundation in the life of society, nation and state to reduce the growing phenomenon of intolerance in society. The results of the research can find effective strategies in building collective public awareness to reject all forms of intolerance and strengthen harmonious and democratic national identity. This research uses a normative juridical method supported by student questionnaires and interviews with resource persons. The material objects in this research include government regulations and policies related to strengthening national insight, while the formal objects are based on the study of Pancasila philosophy as a guideline in shaping an inclusive and equitable social order.